Boron nitride insulating ceramic material and preparation method thereof
Through the raw materials and process flow of specific ratios, boron nitride insulated ceramic materials with excellent performance are prepared, which solves the problems of high cost, poor plasticity, high brittleness and purity requirements of existing materials, and achieves improvement in the performance and cost reduction of materials.
Patent Information
- Application Number
- CN202510072591.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
AI Technical Summary
The existing boron nitride insulated ceramic materials have problems such as high cost, poor plasticity, brittleness, changes in properties at high temperatures and high purity requirements, which limit their promotion in some applications.
Boron nitride insulated ceramic materials with excellent performance are prepared by using specific ratios of raw materials such as boron nitride, aluminum nitride, zirconium oxide, silicon carbide, nano yttrium oxide and cobalt through wet ball milling, drying, low-pressure cold pressing, high-pressure cold pressing molding and hot-pressing sintering.
The strength, density, insulation performance and thermal conductivity of boron nitride insulated ceramic materials are improved, the cost is reduced, the plasticity and temperature resistance of the material are enhanced, and the problem of high material brittleness and purity requirements is solved.
Smart Images

Figure CN119841650A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of engineering ceramic materials, and more particularly to a boron nitride insulating ceramic material and a preparation method thereof. Background Art
[0002] Boron nitride insulating ceramic materials, as an advanced ceramic material with unique physical properties such as high hardness, high thermal stability, excellent electrical insulation performance and excellent chemical stability, are widely used in aerospace (such as rocket engine nozzles, combustion chambers and turbines, etc.), automobile manufacturing (such as cylinder liners, fuel injectors, etc.), electronic information technology (such as high-precision circuits, resistors, capacitors and semiconductor devices), mechanical manufacturing (such as valves, seals and pipes, etc.) and medical (such as artificial joints, dental implants and other medical devices) and other fields.
[0003] However, the boron nitride insulating ceramic materials currently on the market also have some shortcomings and difficulties, mainly including the following aspects:
[0004] 1. High cost: The manufacturing cost of boron nitride insulating ceramic materials is high, which is mainly due to the scarcity of raw materials and the complex processing process. The high cost limits the promotion of boron nitride insulating ceramic materials in some cost-sensitive applications.
[0005] 2. Poor plasticity: Compared with metal materials, the plasticity of boron nitride insulating ceramic materials is poor, which limits their use in some applications that require complex shapes and detailed processing.
[0006] 3. Brittleness: Boron nitride insulating ceramic material is a brittle material that is prone to fracture. Excessive stress concentration or inappropriate load conditions should be avoided during design and use to prevent material damage.
[0007] 4. Performance changes at high temperatures: When the temperature rises, the performance of boron nitride insulating ceramic materials may be affected due to tiny crystal changes, which may cause the material performance to deteriorate or even fail. In addition, boron nitride may also undergo oxidation reactions at high temperatures, further affecting its performance.
[0008] 5. Purity requirements: The production process of boron nitride insulating ceramic materials is complex and has extremely high purity requirements. Even trace amounts of impurities may have a significant impact on the performance of boron nitride, resulting in a decrease in material performance.
[0009] Therefore, how to develop a boron nitride insulating ceramic material with excellent performance, simple preparation and low cost is an urgent problem to be solved by technicians in this field. Summary of the invention
[0010] In view of this, an object of the present invention is to provide a boron nitride insulating ceramic material and a preparation method thereof to solve the deficiencies in the prior art.
[0011] In order to achieve the above object, the present invention adopts the following technical solution:
[0012] A boron nitride insulating ceramic material comprises the following raw materials in parts by weight: 60-80 parts of boron nitride, 40-60 parts of aluminum nitride, 20-30 parts of zirconium oxide, 10-20 parts of silicon carbide, 4-6 parts of nano yttrium oxide and 1-2 parts of cobalt.
[0013] Preferably, the composition is: 60 parts of boron nitride, 40 parts of aluminum nitride, 30 parts of zirconium oxide, 20 parts of silicon carbide, 4 parts of nano yttrium oxide and 1 part of cobalt.
[0014] Preferably, the composition is: 70 parts of boron nitride, 50 parts of aluminum nitride, 25 parts of zirconium oxide, 15 parts of silicon carbide, 5 parts of nano yttrium oxide and 1 part of cobalt.
[0015] Preferably, the composition is: 80 parts of boron nitride, 60 parts of aluminum nitride, 20 parts of zirconium oxide, 10 parts of silicon carbide, 6 parts of nano yttrium oxide and 2 parts of cobalt.
[0016] Furthermore, the particle size of the above-mentioned nano yttrium oxide is 30-50nm.
[0017] The above further beneficial effect is that the addition of rare earth oxides such as yttrium oxide in the traditional method is difficult to significantly improve performance due to its large particle size and difficulty in combining with the boron nitride material. The present invention uses nano-level yttrium oxide, which is easier to combine with the boron nitride material due to its nano-scale, and can well improve strength and density. Moreover, the content of nano yttrium oxide of the present invention is moderate. Too little will not have a tough effect, and too much addition will cause a decrease in temperature resistance and affect the final use.
[0018] In addition, zirconium oxide has high strength, high toughness and excellent crack propagation resistance, silicon carbide has high hardness and excellent wear resistance, and the addition of zirconium oxide and silicon carbide can enhance structural stability, improve temperature resistance, improve thermal expansion performance, increase hardness and wear resistance, and improve mechanical properties.
[0019] Metal cobalt has good thermal conductivity, which can significantly improve the thermal shock resistance of boron nitride insulating ceramic materials, thereby making boron nitride insulating ceramic materials have higher mechanical strength, greatly improving their operating stability and reliability. At the same time, since the amount of metal cobalt used is small and it is coated in boron nitride, the influence of metal cobalt on the insulating properties of boron nitride insulating ceramic materials can be avoided.
[0020] A method for preparing a boron nitride insulating ceramic material specifically comprises the following steps:
[0021] (1) Weighing the raw materials according to the weight proportion of the above-mentioned boron nitride insulating ceramic material, mixing them evenly, and obtaining a mixed material;
[0022] (2) firstly put the mixed material into a wet ball mill, add anhydrous ethanol and perform wet ball milling to obtain a slurry;
[0023] (3) placing the slurry in an oven for drying to obtain a powder;
[0024] (4) firstly subjecting the powder to low-pressure cold pressing and crushing in sequence to obtain granules, then loading the granules into a rubber mold, and subjecting the mold to high-pressure cold pressing by a cold isostatic press to obtain a green body;
[0025] (5) The green body is placed in a sintering furnace for hot pressing and sintering, and then cooled to obtain a boron nitride insulating ceramic material.
[0026] In the present invention, first, the mixed material is mixed with an appropriate amount of anhydrous ethanol and finely ground in a ball mill to obtain a uniform and refined ceramic slurry. This step is to refine the raw material powder and mix it evenly, improve the fluidity of the powder, and lay the foundation for the subsequent molding process.
[0027] Secondly, the ceramic slurry obtained after wet ball milling is dried to remove the water or solvent therein to form a ceramic powder with a certain strength and shape, which can be directly used as the raw material for cold isostatic pressing without sintering.
[0028] Then, the dried ceramic powder is successively subjected to low-pressure cold pressing and crushing to obtain granules, and then the granules are loaded into a rubber mold. Pressure is applied to the rubber mold by a cold isostatic press to rearrange the powder particles in the rubber mold and tightly combine to form a ceramic body of the desired shape.
[0029] Finally, the ceramic body is heated under high temperature and pressure to cause physical and chemical changes between its particles to form a dense ceramic body. During the sintering process, the particles in the ceramic body gradually approach and fuse to form a dense ceramic structure, while reducing porosity and improving mechanical properties and chemical stability.
[0030] Furthermore, in the above step (2), the amount of anhydrous ethanol added is 4%-6% of the mass of the mixture; the speed of the ball mill is 80-150r / min, and the time is 16-20h.
[0031] Furthermore, in the above step (3), the drying temperature is 70-90° C. and the drying time is 2-3 h.
[0032] Furthermore, in the above step (4), the pressure of low-pressure cold pressing is 30-60 MPa; the pressure of high-pressure cold pressing is 100-120 MPa.
[0033] Furthermore, in the above step (5), the procedure of hot pressing sintering is as follows: maintaining the furnace chamber of the sintering furnace in a vacuum state, raising the temperature from room temperature to 1000°C; adjusting the furnace chamber of the sintering furnace to N 2 Atmosphere, heat up from 1000℃ to 1800℃; maintain the temperature of the sintering furnace at 1800℃, the pressure at 10-15Mpa, and sinter at constant temperature and pressure for 1-2h.
[0034] A further beneficial effect of the above method is that hot pressing sintering can improve the purity and density of the product, help optimize the organizational structure, and make it have more excellent physical properties.
[0035] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:
[0036] In the present invention, high-proportion boron nitride, aluminum nitride, zirconium oxide and silicon carbide all have good electrical insulation properties, thereby ensuring the insulation properties of the ceramic material. In addition, although nano yttrium oxide and cobalt have certain electrical conductivity, their content is relatively small, and while not affecting the insulation properties of the ceramic material, they mainly give the ceramic material high strength and high thermal conductivity.
[0037] The boron nitride insulating ceramic material of the present invention has the advantages of high resistivity, good insulation, high bending strength and high thermal conductivity, and can be widely used in high-purity boron nitride crucibles for molten metal, crucibles and support plates for sintering ceramics and powders such as nitride phosphors, silicon nitride, and aluminum nitride, high-temperature furnace electrode insulation parts and protection tubes, and boron nitride insulation components for polysilicon ingot furnaces, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a physical picture of the boron nitride insulating ceramic material of Example 1;
[0039] Figure 2 This is a physical picture of the boron nitride insulating ceramic material of Example 2;
[0040] Figure 3 This is a 1000x scanning electron microscope image of the cross section of the boron nitride insulating ceramic material of Example 2;
[0041] Figure 4 This is a 4000x scanning electron microscope image of the cross section of the boron nitride insulating ceramic material of Example 2. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Example 1
[0044] Boron nitride insulating ceramic material, including the following raw materials by weight: 60kg of boron nitride, 40kg of aluminum nitride, 30kg of zirconium oxide, 20kg of silicon carbide, 4kg of nano yttrium oxide with a particle size of 30nm, and 1kg of cobalt;
[0045] The method for preparing the above-mentioned boron nitride insulating ceramic material specifically comprises the following steps:
[0046] (1) Weighing the raw materials according to the weight of the boron nitride insulating ceramic material, mixing them evenly to obtain a mixed material;
[0047] (2) First, the mixture was placed in a ball mill, 4% anhydrous ethanol was added, and the mixture was ball milled at a speed of 80 r / min for 20 h to obtain a slurry;
[0048] (3) placing the slurry in a drying oven and drying at 70° C. for 3 h to obtain a powder;
[0049] (4) firstly cold-pressing the powder at 30 MPa and crushing it to obtain pellets, then loading the pellets into a rubber mold, and cold-pressing the pellets at 100 MPa by a cold isostatic press to obtain a green body;
[0050] (5) Add the green body into the sintering furnace, keep the furnace chamber of the sintering furnace in a vacuum state, and raise the temperature from room temperature to 1000°C; adjust the furnace chamber of the sintering furnace to N 2 atmosphere, raising the temperature from 1000°C to 1800°C; maintaining the temperature of the sintering furnace at 1800°C and the pressure at 10Mpa, sintering at constant temperature and pressure for 2 hours, taking out and cooling to room temperature, thereby obtaining boron nitride insulating ceramic material.
[0051] Example 2
[0052] Boron nitride insulating ceramic material, including the following raw materials by weight: 70kg of boron nitride, 50kg of aluminum nitride, 25kg of zirconium oxide, 15kg of silicon carbide, 5kg of nano yttrium oxide with a particle size of 40nm, and 1kg of cobalt;
[0053] The method for preparing the above-mentioned boron nitride insulating ceramic material specifically comprises the following steps:
[0054] (1) Weighing the raw materials according to the weight of the boron nitride insulating ceramic material, mixing them evenly to obtain a mixed material;
[0055] (2) First, the mixture was placed in a ball mill, 5% anhydrous ethanol was added, and the mixture was ball milled at a speed of 120 r / min for 18 h to obtain a slurry;
[0056] (3) placing the slurry in a drying oven and drying at 80° C. for 3 h to obtain a powder;
[0057] (4) firstly cold-pressing the powder at 45 MPa and crushing it to obtain pellets, then loading the pellets into a rubber mold, and cold-pressing the pellets at 110 MPa by a cold isostatic press to obtain a green body;
[0058] (5) Add the green body into the sintering furnace, keep the furnace chamber of the sintering furnace in a vacuum state, and raise the temperature from room temperature to 1000°C; adjust the furnace chamber of the sintering furnace to N 2 atmosphere, raising the temperature from 1000°C to 1800°C; maintaining the temperature of the sintering furnace at 1800°C and the pressure at 12Mpa, sintering at constant temperature and pressure for 2 hours, taking out and cooling to room temperature, thereby obtaining boron nitride insulating ceramic material.
[0059] Example 3
[0060] Boron nitride insulating ceramic material, including the following raw materials by weight: 80kg of boron nitride, 60kg of aluminum nitride, 20kg of zirconium oxide, 10kg of silicon carbide, 6kg of nano yttrium oxide with a particle size of 50nm, and 2kg of cobalt;
[0061] The method for preparing the above-mentioned boron nitride insulating ceramic material specifically comprises the following steps:
[0062] (1) Weighing the raw materials according to the weight of the boron nitride insulating ceramic material, mixing them evenly to obtain a mixed material;
[0063] (2) First, the mixture was placed in a ball mill, 6% anhydrous ethanol was added, and the mixture was ball milled at a speed of 150 r / min for 16 h to obtain a slurry;
[0064] (3) placing the slurry in a drying oven and drying at 90° C. for 2 h to obtain a powder;
[0065] (4) firstly cold-pressing the powder material at 60 MPa and crushing it to obtain pellets, then loading the pellets into a rubber mold, and cold-pressing the pellets at 120 MPa by a cold isostatic press to obtain a green body;
[0066] (5) Add the green body into a vacuum bidirectional pressure sintering furnace, keep the furnace chamber of the sintering furnace in a vacuum state, and raise the temperature from room temperature to 1000°C; adjust the furnace chamber of the sintering furnace to N 2 atmosphere, raising the temperature from 1000°C to 1800°C; maintaining the temperature of the sintering furnace at 1800°C and the pressure at 15Mpa, sintering at constant temperature and pressure for 1 hour, taking out and cooling to room temperature, thereby obtaining boron nitride insulating ceramic material.
[0067] Performance Testing
[0068] 1. The physical image of the boron nitride insulating ceramic material obtained in Example 1, and the physical image, 1000 times scanning electron microscope image of the cross section, and 4000 times scanning electron microscope image of the cross section of the boron nitride insulating ceramic material obtained in Example 2 are shown in FIG. Figure 1-4 shown.
[0069] Depend on Figure 1-3 It can be seen that boron nitride insulating ceramic materials can be processed into different shapes according to the requirements of the drawings and used as insulating parts. Moreover, the components are well sintered, with good density and no obvious defects such as cracks and pores.
[0070] 2. The boron nitride insulating ceramic materials prepared in Examples 1-3 were respectively tested for performance. The results are shown in Table 1.
[0071] Table 1 Performance test results of boron nitride insulating ceramic materials of Examples 1-3
[0072]
[0073]
[0074] It can be seen from Table 1 that the various properties of the boron nitride insulating ceramic materials of Examples 1-3 are relatively excellent.
[0075] The above experiments show that the present invention adopts a unique formula and optimizes the composition structure, and the material has the advantages of high resistivity, good insulation, high bending strength and high thermal conductivity.
[0076] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A boron nitride insulating ceramic material, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of boron nitride, 40-60 parts of aluminum nitride, 20-30 parts of zirconium oxide, 10-20 parts of silicon carbide, 4-6 parts of nano yttrium oxide and 1-2 parts of cobalt.
2. The boron nitride insulating ceramic material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 60 parts of boron nitride, 40 parts of aluminum nitride, 30 parts of zirconium oxide, 20 parts of silicon carbide, 4 parts of nano yttrium oxide and 1 part of cobalt.
3. The boron nitride insulating ceramic material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 70 parts of boron nitride, 50 parts of aluminum nitride, 25 parts of zirconium oxide, 15 parts of silicon carbide, 5 parts of nano yttrium oxide and 1 part of cobalt.
4. The boron nitride insulating ceramic material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 80 parts of boron nitride, 60 parts of aluminum nitride, 20 parts of zirconium oxide, 10 parts of silicon carbide, 6 parts of nano yttrium oxide and 2 parts of cobalt.
5. A boron nitride insulating ceramic material according to any one of claims 1 to 4, characterized in that: The particle size of the nano yttrium oxide is 30-50nm.
6. A method for preparing a boron nitride insulating ceramic material, characterized in that: The specific steps include: (1) Weighing the raw materials according to the weight proportion of the boron nitride insulating ceramic material according to any one of claims 1 to 5, mixing them uniformly to obtain a mixture; (2) firstly put the mixed material into a wet ball mill, add anhydrous ethanol and perform wet ball milling to obtain a slurry; (3) placing the slurry in an oven for drying to obtain a powder; (4) firstly subjecting the powder to low-pressure cold pressing and crushing in sequence to obtain granules, then loading the granules into a rubber mold, and subjecting the rubber mold to high-pressure cold pressing by a cold isostatic press to obtain a green body; (5) The green body is placed in a sintering furnace for hot pressing and sintering, and then cooled to obtain the boron nitride insulating ceramic material.
7. The method for preparing a boron nitride insulating ceramic material according to claim 6, characterized in that: In step (2), the amount of anhydrous ethanol added is 4%-6% of the mass of the mixture; the rotation speed of the ball mill is 80-150r / min, and the time is 16-20h.
8. The method for preparing a boron nitride insulating ceramic material according to claim 6, characterized in that: In step (3), the drying temperature is 70-90° C. and the drying time is 2-3 hours.
9. The method for preparing a boron nitride insulating ceramic material according to claim 6, characterized in that: In step (4), the pressure of the low-pressure cold pressing is 30-60 MPa; the pressure of the high-pressure cold pressing is 100-120 MPa.
10. The method for preparing a boron nitride insulating ceramic material according to claim 6, characterized in that: In step (5), the hot pressing sintering procedure is as follows: maintain the furnace chamber of the sintering furnace in a vacuum state, and raise the temperature from room temperature to 1000°C; adjust the furnace chamber of the sintering furnace to a N2 atmosphere, and raise the temperature from 1000°C to 1800°C; maintain the temperature of the sintering furnace at 1800°C and the pressure at 10-15Mpa, and sinter at a constant temperature and pressure for 1-2h.